Study of the Mechanism Underlying the Antihypertensive Effects of Eucommia ulmoides and Tribulus terrestris Based on an Analysis of the Intestinal Microbiota and Metabonomics. (6th November 2020) - Qi, Ying-Zi; Yang, Xue-Song; Jiang, Yue-Hua; Shao, Lin-Lin; Jiang, Ling-Yu; Yang, Chuan-Hua
Abstract : The combination of Eucommia ulmoides and Tribulus terrestris (ET) has been widely utilized in clinical practice for thousands of years, but the mechanism underlying its efficacy has not been elucidated to date. This study attempted to investigate the role played by the intestinal microbiota and fecal metabolism in the response of elderly spontaneous hypertensive rats (SHRs) to ET administration as a treatment for hypertension. Fourteen male spontaneously hypertensive rats (SHRs, 18 months old) were randomly divided into an ET group and an SHR group, and 7 Wistar-Kyoto (WKY) rats of the same age were employed as the control group. The ET group was intragastrically administered 1.0 g/kg/d ET for 42 days, and SHRs and WKY rats were administered an equal amount of normal saline intragastrically. The intestinal microbiota and fecal metabolism were analyzed by 16S rRNA sequencing and the GC-MS (gas chromatography-mass spectrometry)/MS assay. ET treatment decreased blood pressure steadily, improved the colonic tissue morphology, and changed the structure and composition of the imbalanced microbiota in SHRs. Specifically, ET treatment increased the abundance of Eubacterium, which might be one of the target microbes for ET, and had a negative correlation with the levels of α -tocopherol, chenodeoxycholic acid, and deoxycholic acid according to the Spearman correlation analysis. The change in the intestinal microbiota affected the fecal metabolic pattern of SHRs. Eight potential biomarkers were determined to be primarily enriched in ABC transporters, phenylalanine metabolism, central carbon metabolism in cancer, purine metabolism, and protein digestion and absorption. The correlation analysis demonstrated that the abundance of Eubacterium and the decreased levels of α -tocopherol, chenodeoxycholic acid, and deoxycholic acid in the ET group were highly correlated. Our results suggest that ET has a good antihypertensive effect, which may be driven by the intestinal microbiota and their beneficial metabolites. The results of this study may help to elucidate the antihypertensive mechanism of ET.